Human Resource Management Quality as a Determinant of Customer Satisfaction with Service Quality as a Mediator - Mardiyana, Mardiyana; Ratnasari, Ani; Nurhidayah, Rika (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2025)
This study examines the impact of digital human resource management (HRM) quality on customer satisfaction, with service quality acting as a mediating variable, within Indonesia’s e-commerce landscape. Employing a quantitative approach and structural equation modeling (SEM), data were collected from 300 Shopee users across multiple regions. The results indicate that digital HRM quality significantly influences customer satisfaction (β = 0.387, p < 0.001), with employee digital competence emerging as the most influential indicator. Moreover, service quality partially mediates this relationship, suggesting that internal HRM capabilities shape external consumer perceptions and experiences. The findings support the relevance of theoretical models such as the Resource-Based View (RBV), Service-Dominant Logic (SDL), and digital transformation theory in the Southeast Asian context. This study underscores the strategic value of human capital in digital markets and highlights the importance of continuous investment in employee digital skills. Practical implications are provided for e-commerce firms aiming to align HRM strategies with customer experience management to sustain competitiveness in dynamic digital environments.